2017
DOI: 10.1136/injuryprev-2016-042174
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with unintentional house fire incidents, injuries and deaths in high-income countries: a systematic review

Abstract: This best evidence synthesis indicates that several resident and property characteristics are associated with risk of experiencing house fire incidents, injuries or death. These findings should be considered by the Fire and Rescue Services and others with a role in fire prevention. Future research should adopt robust, standardised study designs to permit meta-analyses and enable stronger conclusions to be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…If a similar pattern exists regarding the possession and knowledge of fire safety equipment in the general population, this could serve as a potential explanation for the socio-demographic differences in mortality and aid in the identification of prevention measures. It could also help clarify the conflicting results between epidemiological studies of the social determinants of residential fires and studies of fire mortality [32].…”
Section: Introductionmentioning
confidence: 99%
“…If a similar pattern exists regarding the possession and knowledge of fire safety equipment in the general population, this could serve as a potential explanation for the socio-demographic differences in mortality and aid in the identification of prevention measures. It could also help clarify the conflicting results between epidemiological studies of the social determinants of residential fires and studies of fire mortality [32].…”
Section: Introductionmentioning
confidence: 99%
“…According to participants' experiences, the individual characteristics including vulnerable age groups, disabilities and patients, high-risk behaviors such non-consideration of safety and its negligence, are among the factors that are obstacles of safety against re. In many studies it has been consistently reported that buildings with more elderly, disabled, and sick people are more likely to be affected by re and death (13,(39)(40)(41). The lack of attention to the value of the people's lives especially the vulnerable groups in incidents and res seems to be one of the causes of injuries in these groups.…”
Section: Resident Characteristics and Behaviorsmentioning
confidence: 99%
“…Although the literature suggests that socioeconomic deprivation increases the risk of fire incidents and related casualties overall, 11,15,21 mixed findings across studies render the association between educational attainment, residential fire incidents and casualties inconclusive. 21,22 However, 2 recent studies showed that higher level of education was associated with increased risk of residential fire incidents, 23,24 consistent with our findings. Our results for employment status are consistent with those of previous studies.…”
Section: Openmentioning
confidence: 99%
“…Our results for employment status are consistent with those of previous studies. 21,22,25 Although the absence of a relation between income and risk of residential fire incidents and casualties was surprising, recent studies have also shown no association. 23,24,26 This may be explained by various financial support and fire safety programs delivering free smoke detectors and education, which may limit the influence of poverty on some risk factors for residential fires in Canada, but additional studies are needed.…”
Section: Openmentioning
confidence: 99%
See 1 more Smart Citation